2009
DOI: 10.1017/s1041610209009065
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and suicidal behavior: a review of the literature

Abstract: Further research should be undertaken to examine how rates of suicide and self-harm change during the course of the illness and vary according to the specific sub-type of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
3
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(150 citation statements)
references
References 125 publications
(155 reference statements)
8
129
3
10
Order By: Relevance
“…In a recent review of suicide in dementia, preserved insight was a putative risk factor. 27 Participants in the PREDICT-HD Study are not informed of the HD diagnosis/phenoconversion by the research team, but some with more symptoms may have been given a formal diagnosis of HD onset by their treating HD specialist. Because group D had slightly more progression of HD, more symptoms would be expected, but group B although undiagnosed was symptomatic as well.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent review of suicide in dementia, preserved insight was a putative risk factor. 27 Participants in the PREDICT-HD Study are not informed of the HD diagnosis/phenoconversion by the research team, but some with more symptoms may have been given a formal diagnosis of HD onset by their treating HD specialist. Because group D had slightly more progression of HD, more symptoms would be expected, but group B although undiagnosed was symptomatic as well.…”
Section: Resultsmentioning
confidence: 99%
“…While dementia in general is not a strong risk factor for late-life suicide (36), these observations raise the possibility that for a subgroup, the interval of increased risk for suicidal behavior may be at its prodromal or early stage (37). This study is not designed to specifically investigate suicide risk in elderly with cognitive impairment, because we excluded subjects diagnosed with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies which did not provide data to calculate the proportions of death due to suicide or any direct calculation of rate, some [18,19] , but not all [20] , studies suggested an association between suicide and HD. The higher risk of suicide observed in HD has not been demonstrated for other dementias, for which most evidence suggests a lower rate of suicide compared to the general population [21] .…”
Section: Introductionmentioning
confidence: 88%